Antecedents of entrepreneurial intentions in smart city of Neom Saudi Arabia: Does the entrepreneurial education on artificial intelligence matter? - Mohammed T. Nuseir; Muhammad Farhan Basheer; Ahmad Aljumah (Cogent Business & Management, 2020)
The main purpose of this empirical study is to explore the entrepreneurial self-efficacy, and entrepreneurial competency as antecedents to the entrepreneurial intentions in smart city of Neom Saudi Arabia. Additionally, the study has also examined the mediating role of entrepreneurial education on artificial intelligence in the relationship between the entrepreneurial self-efficacy, entrepreneurial competency, and the entrepreneurial intentions in smart city of Neom Saudi Arabia. The study has employed the SEM-PLS for the data analysis. A sample based on 550 students from private (n = 291, 52.9 %) and public universities (n = 259, 47.1 %) of KSA were randomly selected. The entrepreneurial self-efficacy, and entrepreneurial competency are reported to have a positive and significant influence on entrepreneurial intentions. The entrepreneurial education on artificial intelligence, medicate the relationship between the entrepreneurial competency, entrepreneurial self-efficacy, and entrepreneurial intentions The model is contextually suitable for motivating individuals to become self-sufficient and for enabling them to harness their creativity through entrepreneurial and profit-driven endeavors in smart cities. This study has significant implications for entrepreneurs, practitioners, and governments alike. The findings provide a guideline for governments in establishing an environment that supports the individual drive to embark on entrepreneurial endeavors. Among the stimulus for encouraging entrepreneurship include the provision of loans with reasonable interest rates and knowledge sharing sessions by prominent entrepreneurs. Drawing inferences from the empirical findings and discussions, this present study has made appreciable theoretical contributions to the existing body of literature, specifically, in the area of entrepreneurial intentions in smart city.
Keywords: 650; Entrepreneurship; education; smart city; artificial intelligence; KSA